The effect of SDL and creative thinking on learning outcomes in Pancasila education material - Delisma Siregar; Anita Yus; Daulat Saragi (Inovasi Kurikulum, 2025)
This study is motivated by the importance of improving students’ learning outcomes in Pancasila Education at the elementary school level. The purpose of this research is to examine the effect of the Self-Directed Learning model on students’ learning outcomes, as well as the interaction between the learning model and creative thinking skills on learning outcomes. This research employed a quantitative method with a quasi-experimental design. The sample was selected using total sampling, where class IVA served as the experimental group applying the Self-Directed Learning model, and class IVB as the control group using the Direct Instruction model. Research instruments included tests and questionnaires to measure learning outcomes and creative thinking skills. The results of the ANOVA analysis indicated that the Self-Directed Learning model had a significant effect on improving students’ learning outcomes. Additionally, the interaction between the learning model and creative thinking skills also had a significant impact on learning outcomes. These findings demonstrate that the Self-Directed Learning model is effective in enhancing students’ learning outcomes in Pancasila Education.   Abstrak Penelitian ini dilatarbelakangi oleh pentingnya peningkatan hasil belajar peserta didik pada materi Pendidikan Pancasila di sekolah dasar. Tujuan penelitian ini adalah untuk mengetahui pengaruh model pembelajaran Self-Directed Learning terhadap hasil belajar peserta didik, serta interaksi antara model pembelajaran dan kemampuan berpikir kreatif terhadap hasil belajar. Penelitian ini menggunakan metode kuantitatif dengan desain quasi eksperimen. Sampel diambil secara total sampling, di mana kelas IVA sebagai kelas eksperimen menerapkan model Self-Directed Learning dan kelas IVB sebagai kelas kontrol menggunakan model Direct Instruction. Instrumen penelitian berupa tes dan angket digunakan untuk mengukur hasil belajar dan kemampuan berpikir kreatif peserta didik. Hasil analisis ANAVA menunjukkan bahwa model Self-Directed Learning berpengaruh signifikan terhadap peningkatan hasil belajar peserta didik. Selain itu, kemampuan berpikir kreatif dan interaksi antara model pembelajaran dengan kemampuan berpikir kreatif juga memberikan pengaruh signifikan terhadap hasil belajar. Temuan ini menunjukkan bahwa model Self-Directed Learning efektif dalam meningkatkan hasil belajar peserta didik pada materi Pendidikan Pancasila. Kata Kunci: berpikir kreatif; hasil belajar; self-directed learning